Escola de tempo integral: da convenção à participação - Vetorazzi, Nilcéia Gomes (2011)
This study examines the full-time school implementation proposal started in 2007 by the Public Schools of São José dos Campos - SP. The Jacyra Vieira Baracho Elementary School follows this proposal since 2009 and was chosen as a case study. The goal is to measure the impact of the full-time school on both students and the related community needs using the following tools: documental analysis, interviews and on-site observations. The research starting points are the political context and the education and the school realities.The results show that the following aspects need improvements in order to facilitate the full-time public schools implementation: school structure and didatic materials, teacher salaries and teacher trainings